EFEKTIVITAS KOMUNIKASI TERAPEUTIK BIDAN TERHADAP PENURUNAN KECEMASAN IBU HAMIL MENJELANG PERSALINAN DI PMB LILIS SURYANI SST DEPOKTAHUN 2023 - Lucyana Jenny Vera; Rizkiana Putri; Astrid Novita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The incidence of childbirth anxiety worldwide is estimated at 14%, and primiparous have a greater level of fear compared to multiparous mothers. Anxiety facing childbirth is fluctuating, in early pregnancy is relatively low and increases with increasing gestational age. In Indonesia there are 373,000 pregnant women, and those who experience anxiety in the face of childbirth as many as 107,000 (28.7%) pregnant women. This study aims to analyze the effectiveness of midwives' therapeutic communication on reducing anxiety of pregnant women before childbirth at PMB Lilis Suryani SST in 2023. This research is a quasi-experiment and the research design used is one group pre-test-post test design, with the sample used amounting to 44 respondents. The results of this study based on statistical analysis of the Paired Sample T-Test showed that there was a significant effectiveness of therapeutic communication on reducing anxiety in pregnant women before delivery, namely P Value = 0.000 (P Value < 0.05). The conclusion of this study is that therapeutic communication is effective for lowering anxiety in pregnant women before delivery. Suggestions for PMB to make therapeutic communication SOPs so that health workers can apply them properly to reduce anxiety for pregnant women.